What do scientists want: money or fame? - Devrim Göktepe-Hultén; Prashanth Mahagaonkar (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
What makes scientists patent and disclose inventions to employers? Using a new dataset on Max Planck scientists, we explore their motivations to patent and/or disclose inventions. We propose that patenting need not be used for monetary benefits. Scientists value reputation as important use patenting and disclosures as a signal to gain it. We find that it is not monetary benefits that drive patenting and disclosures but expectation of reputation. We also find that experience with the employer matters for disclosure of inventions. This may imply that patents are indeed used as information transfer mechanisms with prime motivation being reputation.
Keywords: 330; University patenting; inventors; incentives; Wissenschaftler; Erfindung; Motivation; Prestige; Patent; Informationsverbreitung; Deutschland